TRAINING DESIGN IN REDUCING SOCIAL ANXIETY IN INTROVERTED PERSONALITY STUDENTS WITH BEHAVIORAL TECHNIQUES REHEARSAL - Hardiansyah, Fathoni; Erawati, Desi; Mz, Ihsan (EDUCATIONE, 2023)
Students who have social anxiety will affect lecture activities as well as daily activities. Students who experience social anxiety while undergo lectures could weaken memory skills, have difficulty focusing and have poor academic performance. This study wanted to examine how training design reduces social anxiety in students with introverted personalities using behavior rehearsal techniques. This study used the research and development methods. This study developed a training design using behavior rehearsal techniques with predetermined steps, namely potential and problems, collecting literature study data, product design, design validation, design revision, and product/design trials. The design validation process was carried out by 3 experts validators who are competent in the field of guidance and counseling. The participants in this study were 10 students of IAIN Palangka Raya with the criteria of having social anxiety with an introverted personality. The result of this study was acceptability/acceptance of expert validators obtained an assessment score of 88% with very good criteria with slight revisions. The training design developed to reduce social anxiety in introverted students was decent and could be used with some revisions.